Inter-Services Communication in Child Welfare: The Interplay of Age, Work-group Identification, Trust and Self-efficacy - Berlanda, Sabrina; Pedrazza, Monica; Mori, Luca; de Cordova, Federica; Fraizzoli, Marta (Italian Sociological Review, 2018)
The present study involves 157 social workers employed in two public child welfare agencies of North-East Italy. Recent approaches (Pedrazza, Berlanda, 2017; Pedrazza, Sartori, Berlanda, 2017) show that social work in child welfare agencies requires communication skills and social competence, such as work-group identification and trust. These studies show that perceived self-efficacy represents an important element of inter-service communication. The aim of our study is to attempt to identify the role of age, work-group identification and trust in predicting social workers’ self-efficacy in emotion regulation, procedural self-efficacy, self-efficacy in seeking support, and self-efficacy in professional communication. Assuming the causal relationship between variables, we propose multiple linear regression analysis in order to identify antecedents of self-efficacy.